Production of Al-Ti-C grain refiners with the addition of elemental carbon - Gezer, Berke Turgay; Toptan, Fatih; Daglilar, Sibel; Kerti, Isil (ELSEVIER SCI LTD, 2010)
Grain refining process used in aluminium alloys, has an important role for preventing columnar, coarse grains and encouraging fine, equiaxed grain formation. Al-Ti-B grain refiners are widely used as aluminium grain refiners despite the problems in application Al-Ti-C refiners have an increasing demand in recent years. In the present work, Al-Ti-C grain refiners with different Ti:C ratios were produced by insitu method with the addition of elemental carbon. Microstructures were characterised by optic microscope and scanning electron microscope equipped with energy dispersive spectroscopy. The effects of temperature, holding time and Ti:C ratio on the grain refinement process were investigated and optimum conditions were determined. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Aluminium; Casting; Grain refiner; Insitu production; Titanium; REFINING EFFICIENCY; ALUMINUM; Materials Science